2015
DOI: 10.1088/1367-2630/17/1/013028
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electronic properties of manganese-doped Bi2Te3epitaxial layers

Abstract: We show that in manganese-doped topological insulator bismuth telluride layers, Mn atoms are incorporated predominantly as interstitials in the van der Waals gaps between the quintuple layers and not substitutionally on Bi sites within the quintuple layers. The structural properties of epitaxial layers with Mn concentration of up to 13% are studied by high-resolution x-ray diffraction, evidencing a shrinking of both the in-plane and out-of plane lattice parameters with increasing Mn content. Ferromagnetism set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 27 publications
2
33
1
Order By: Relevance
“…Thus, small shrinks of the lattice are caused by the neighboring Te atoms. This result is compatible with the XRD data measured by Růžička et al…”
Section: Examples Of the Data Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, small shrinks of the lattice are caused by the neighboring Te atoms. This result is compatible with the XRD data measured by Růžička et al…”
Section: Examples Of the Data Analysissupporting
confidence: 93%
“…By adding transition metals, it changes to show a TI behavior. The existence of the Dirac cone in the surface state electronic density of states was confirmed in Mn‐doped Bi 2 Te 3 by an angle‐solved photoemission spectroscopy investigation …”
Section: Examples Of the Data Analysismentioning
confidence: 89%
“…11 The main goal of achieving room-temperature ferromagnetism in homogeneously doped 3D TIs has therefore proven difficult to achieve. 14 Although Mn doped Bi 2 Te 3 crystals and thin films with doping concentrations of up to 10% were found to be ferromagnetic with Curie temperatures of around 10 K, 15 it is not clear if ferromagnetism is due to secondary, undesirable Mn-containing phases or the homogeneous doping of Mn into the Bi 2 Te 3 matrix, i.e., as a substitutional dopant. Due to the layered crystal structure of these materials, several possible lattice sites exist for the incorporation of magnetic dopants.…”
mentioning
confidence: 99%
“…These include substitutional incorporation on Bi or Te sites within the QLs, as well as interstitial incorporation within the QLs, and the incorporation in the van der Waals gap between the QLs. 15 In these ternary systems, it is of great importance to preserve the overall bulk electronic properties upon doping, and, moreover, to reduce the defect densities in general.…”
mentioning
confidence: 99%
“…However, little is known about the real structure and crystal quality of Bi m X n thin films grown by molecular beam epitaxy (MBE). In our previous papers [14][15][16] we investigated the crystal structure of MBE grown epitaxial Bi 2 Te 3 and Mn-doped Bi 2 Te 3 layers using highresolution x-ray diffraction (HRXRD) and x-ray absorption spectroscopy (EXAFS) and angle-resolved photoelectron spectroscopy (ARPES). We found that the chemical composition, crystal structure as well as the crystal quality substantially depend on the excess flux of Te during the MBE growth.…”
Section: Introductionmentioning
confidence: 99%